Eksplorasi Daging Analog Dari Berbagai Jenis Protein Nabati - Lia Wildatus Sholihah,; Ikha Handayani,; Usi Susila,; Jufrinaldi, Jufrinaldi (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2024)
Analog meat is a sustainable solution designed to mimic the texture, taste and appearance of animal meat using the main ingredient of plant protein. Along with increasing awareness of the environmental impact of the livestock industry and the need for alternative protein sources, the development of plant-based protein-based meat analogues has become very relevant. Vegetable proteins commonly used in making meat analogues include soybeans, peas and microalgae. This journal reviews several unique characteristics in protein content, texture, taste, and challenges of each of these ingredients. Soybeans, having a high protein content, produce meat analogues with a taste and texture resembling beef through the extrusion process and Maillard reaction. Peas, have a lower protein content, but contribute to the creation of a meat analogue with its own characteristics. Microalgae, such as Spirulina and Chlorella, contain protein as well as essential amino acids, and offer a superior nutritional profile compared to other protein sources. This research aims to explore the potential and challenges in developing meat analogues based on soybeans, peas and microalgae.